2013
DOI: 10.1371/journal.pone.0063873
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Infection Elicits Heat Shock Protein 72 Release from Pleural Mesothelial Cells

Abstract: Heat shock protein 70 (HSP70) has been implicated in infection-related processes and has been found in body fluids during infection. This study aimed to determine whether pleural mesothelial cells release HSP70 in response to bacterial infection in vitro and in mouse models of serosal infection. In addition, the in vitro cytokine effects of the HSP70 isoform, Hsp72, on mesothelial cells were examined. Further, Hsp72 was measured in human pleural effusions and levels compared between non-infectious and infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…These authors also reported that HSP72 levels of CSF were higher in bacterial meningitis than in aseptic meningitis [17]. In another study, Varano Della Vergiliana et al reported that HSP72 levels were significantly higher in the exudates than in the transudates of patients with pleural effusion and that the reason for the increased HSP72 was the stimulation of mesothelial cells by the pneumococcal products [18]. Similarly, Davies et al reported that the HSP70 released from macrophages was due to exposure to bacterial products of Escherichia coli in cell culture [10].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These authors also reported that HSP72 levels of CSF were higher in bacterial meningitis than in aseptic meningitis [17]. In another study, Varano Della Vergiliana et al reported that HSP72 levels were significantly higher in the exudates than in the transudates of patients with pleural effusion and that the reason for the increased HSP72 was the stimulation of mesothelial cells by the pneumococcal products [18]. Similarly, Davies et al reported that the HSP70 released from macrophages was due to exposure to bacterial products of Escherichia coli in cell culture [10].…”
Section: Discussionmentioning
confidence: 90%
“…The expression of HSP70 increases in inflammation as well as in the other cellular stress conditions, such as oxidative stress and hypoxia, in various cells [5,16]. HSP72, a member of the HSP70 family, has been shown to increase in a variety of body fluids due to bacterial infections [17,18]. Tang et al [17] evaluated HSP72 levels in cerebrospinal fluid (CSF) of the patients who underwent lumbar puncture due to the suspicion of meningitis and found that the CSF of patients with meningitis was characterized by significantly elevated levels of HSP72 in comparison to patients without meningitis based on CSF assessment.…”
Section: Discussionmentioning
confidence: 99%
“…SFBS-F) and 0.4 μg/mL hydrocortisone (Sigma-Aldrich) [ 16 ]. Met-5A mesothelial cells (ATCC ® CRL-9444) were cultured in the same formulation of DMEM as the primary mesothelial cells, but without hydrocortisone and using 10% FBS [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence indicates that bacterial components and metabolites specifically control the expression of HSPs ( 9 , 10 ). HSP72 can be detected in quite a few body fluids, such as pleural fluid ( 11 ), cerebrospinal ( 12 ), synovia ( 12 ), bronchoalveolar lavage fluid ( 13 ), and serum ( 14 ). Recent evidence indicated that the concentration of the stress-inducible HSP72 homolog, HSP70, increased in patients with heart failure ( 15 ) and atherosclerosis ( 16 ).…”
Section: Introductionmentioning
confidence: 99%